2015
DOI: 10.3390/f6061858
|View full text |Cite
|
Sign up to set email alerts
|

Post-Fire Seedling Recruitment and Morpho-Ecophysiological Responses to Induced Drought and Salvage Logging in Pinus halepensis Mill. Stands

Abstract: Salvage logging is the commonest post-fire emergency action, but has unclear ecological effects. In the Mediterranean Basin, drought periods and fire regimes are changing and forest management should be adapted. In summer 2009, a mid-high severity fire burned 968 ha of Aleppo pine (Pinus halepensis Mill.) forest in southeast Spain, which was submitted to salvage logging six months later. In spring 2010, plots were set in untreated and logged areas to monitor the recruitment and survival of the main tree specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…Unexpectedly, there were no interactive (synergistic) effects between fire and salvage logging after a single large high-severity fire (F vs. F-iSL and F-dSL), as the removal of the burned wood did not decrease pine seedling recruitment and performance more than did fire alone. Particularly, in the studied stands, immediate (<1 year after fire) salvage logging had no detrimental effects on the natural regeneration of the vegetation; contrarily to previous results by other authors that demonstrated the negative impact of harvesting operations on pine seedling emergence and mortality, plant species composition and diversity, shrub regrowth, and plant facilitative interactions (e.g., Castro et al, 2011;Leverkus et al, 2014;Lindenmayer & Noss, 2006;Moya et al, 2015). Firstly, the high number of mature trees bearing serotinous cones in the studied maritime pine population (Tapias et al, 2004) very likely resulted in a large number of recruited seedlings (Calvo et al, 2008;Hernández-Serrano et al, 2013) that were either very abundant to counterbalance mortality (Martínez-Sánchez et al, 1999) or not seriously damaged by the prompt harvesting operations, as trunks were manually handled without heavy machinery (see Blair et al, 2016;Castro et al, 2011;Leverkus et al, 2014, and references therein).…”
Section: Cumulative and Interactive Effects Of Fire And Salvage Loggingsupporting
confidence: 68%
See 2 more Smart Citations
“…Unexpectedly, there were no interactive (synergistic) effects between fire and salvage logging after a single large high-severity fire (F vs. F-iSL and F-dSL), as the removal of the burned wood did not decrease pine seedling recruitment and performance more than did fire alone. Particularly, in the studied stands, immediate (<1 year after fire) salvage logging had no detrimental effects on the natural regeneration of the vegetation; contrarily to previous results by other authors that demonstrated the negative impact of harvesting operations on pine seedling emergence and mortality, plant species composition and diversity, shrub regrowth, and plant facilitative interactions (e.g., Castro et al, 2011;Leverkus et al, 2014;Lindenmayer & Noss, 2006;Moya et al, 2015). Firstly, the high number of mature trees bearing serotinous cones in the studied maritime pine population (Tapias et al, 2004) very likely resulted in a large number of recruited seedlings (Calvo et al, 2008;Hernández-Serrano et al, 2013) that were either very abundant to counterbalance mortality (Martínez-Sánchez et al, 1999) or not seriously damaged by the prompt harvesting operations, as trunks were manually handled without heavy machinery (see Blair et al, 2016;Castro et al, 2011;Leverkus et al, 2014, and references therein).…”
Section: Cumulative and Interactive Effects Of Fire And Salvage Loggingsupporting
confidence: 68%
“…While twice-burned plots had (1) high density of immature pines with low reproductive ability (i.e., small canopy seed bank; Espelta et al, 2008), (2) a well-developed shrub layer, and, thus, (3) greater regrowth of the understorey. In addition, no differences between once-and twice-burned plots were observed for the recovery of obligate seeder shrubs that are tolerant to high-severity fires and variable water conditions (Moya et al, 2015), and slowly regenerated from their persistent soil seed banks (Pausas & Keeley, 2014).…”
Section: Cumulative and Interactive Effects Of Fire And Salvage Loggingmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results indicated high SR rates in summer, which is associated with higher soil surface temperature levels and microclimate aspects [42,43]. In addition, Austin and Vivanco [44], or Brandt et al [45], have observed that an increase in UV radiation in soil favours litter decomposition, which may be due to microbial facilitation [46], and consequently increases SR [47].…”
Section: Discussionsupporting
confidence: 52%
“…The severely burned site had the most stable water availability of the three sites across time, likely due to low total biomass and competition, but the shallow‐rooted pine saplings were not as able to capitalize on this advantage as the deep‐rooted resprouts. The roots of regenerating pines are likely restricted to the upper part of the profile, whereas the resprouting oaks have deep root systems remaining from mature trees (Clemente, Rego, & Coreia, ; Moya, de las Heras, López‐Serrano, & Ferrandis, ; Vilagrosa, Hernandez, Luis, Cochard, & Pausas, ). The resprouts' greater root : shoot ratios help increase hydraulic efficiency over that of mature trees.…”
Section: Discussionmentioning
confidence: 99%